London: a social and cultural history, 1550 - 1750 - Bucholz, R. O. (Cambridge Univ. Press, 2012)
"Between 1550 and 1750 London became the greatest city in Europe and one of the most vibrant economic and cultural centres in the world. This book is a history of London during this crucial period in its rise to world-wide prominence, during which it dominated the economic, political, social and cultural life of the British Isles. London incorporates the best recent work in urban history, contemporary accounts from Londoners and tourists, and fictional works featuring the city in order to trace London's rise and explore its role as a harbinger of modernity, while examining how its citizens coped with those achievements. London covers the full range of life in London, from the splendid galleries of Whitehall to the damp and sooty alleyways of the East End. Readers will brave the dangers of plague and fire, witness the spectacles of the Lord Mayor's Pageant and the hangings at Tyburn, and take refreshment in the city's pleasure-gardens, coffee-houses and taverns"--